Approach for Diagnostic and Treatment of Chronic Diarrhea Caused by Hookworm Infection - Cekli Wahyuwidowati; Achmad Fauzi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2012)
Chronic diarrhea has various etiologies. One of the causes includes parasitic infection, such as hookworm. Human hookworm infections are caused by the blood-feeding intestinal nematodes (Ancylostoma duodenale and Necator americanus). A 54-year-old male was admitted to Cipto Mangunkusumo Hospital with a chief complaint of diarrhea since one month before hospital admission. He experienced diarrhea more than five times a day, without blood and mucus. The stool appearance was yellow without bubbles. He also noted decreased appetite and weight loss. The remarkable physical finding was pain in whole abdomen. Laboratory results showed leukocytosis; while the feces analysis showed bacteria, leukocytes and Gram-negative bacilli. Colonoscopy examination revealed a lot of worms in the colon with multiple ulcers. Histopathological findings indicated colitis with plasma and eosinophils cells in the lamina propia. Parasitology analysis confirmed the hookworms (Necator americanus). The patient was given intravenous fluid, albendazole 400 mg in three consecutive days. The patient’s clinical condition was improved and he was subsequently discharged after seven days of hospitalization. During the follow up at outpatient clinic, the patient was in healthy condition. This is a demonstrative case of human hookworm infection that cause chronic diarrhea. Colonoscopy plays important role for evaluating and finding the etiology of chronic diarrhea. Proper treatment with albendazole has been proven to be effective in eradicating hookworm infection. Keywords: diarrhea, parasite, hookworm